THE RELATIONSHIP AMONG THE INTENSITY OF LEARNING, SELF REGULATED LEARNING AND PARENT’S ATTENTION WITH STUDENTS MATHEMATICS LEARNING OUTCOMES - Novita Yanti; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
Based on the observation in State Junior High School 9 Yogyakarta (SMP Negeri 9 Yogyakarta) obtained some information that the lack of student learning intensity, self-regulated learning is still low, and the lack of attention from parents in learning activities. This study aims to determine the presence or absence of a positive relationship between and significant relationship among the intensity of learning, self-regulated learning, and parent’s attention with students mathematics learning outcomes of class VIII SMP Negeri 9 Yogyakarta academic year 2016/2017. The population in this research was the students of VIII grade in SMP Negeri 9 Yogyakarta in 2016/2017, consisting of class VIIIA, VIIIB, VIIIC, VIIID, VIIIE, and VIIIF totaling 206 students. Samples were taken from VIIIA as the research sample class and with the random sampling technique. The researcher uses a questionnaire method to collect the data intensity of learning, independence learning, parent’s attention, and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between the intensity of learning, independent learning, and parents' attention with mathematics learning outcomes in students class VIII of SMP Negeri 9 Yogyakarta academic year of 2016/20167. It is showed by Fcount Ftable is 7,5791 > 2,9223 with R = 0,6566 and R2 = 0,4311 with , with RC = , RC = and RC = 20,84 , EC = , EC = and EC = .